DIMENSI KEMANUSIAAN DALAM PENDIDIKAN ISLAM (Perpektif Al-Quran) - Thoha, Mohammad (STAIN Pamekasan, 2010)
Abstract: Human beings as the creatures of Allah have two complementary elements, namely physical and spiritual. On another dimension, humans are creatures who need education. In line with the effort to guide the entire human potentials, Islam provides throughly attention to the existence of humans, so that there is nothing left and neglected, in terms of both physical and spiritual, good mental life, and all their activites on the earth. The following article describes some of the titles and functions of the human beings in al-Quran to portray the human potentials that can be developed towards the realization of human existence as the highest Gods caliph on earth.